One-pot synthesis and negative ion mass spectrometric investigation of a densely functionalized cinnoline. Issue 50 (16th December 2015) - Lambert, Daniel J.; Parikh, Nigam; Messham, Stephen J.; Edwards, Giles; van Truong, Hieu; Dempster, Nicola M.; Drew, Michael G.B.; Nahar, Lutfun; Sarker, Satyajit D.; Ismail, Fyaz M.D.
Graphical abstract: Abstract: Known, densely substituted 3-amino-5, 7, 8-trichloro-6-hydroxycinnoline-4-carbonitrile was synthesized using a one pot synthetic protocol under base-mediated conditions in a polar medium. Condensation of excess malononitrile with chloranil in ethanol at reflux gave quinone methide—2-(2, 4, 5-trichloro-3-hydroxy-6-oxocyclohexa-2, 4-dien-1-ylidene)malononitrile which was isolated as the triethylamine salt. This represents an atom efficient, simple, and effective procedure for the preparation of a highly substituted cinnolines that may serve as relay materials for antimalarial prototypes.